Interdisciplinary stratified care for low back pain - Caeiro, Carmen (2019)
BACKGROUND AND OBJECTIVE: The SPLIT project aims to introduce an interdisciplinary stratified model of care for patients with low back pain. This study aimed to explore the acceptability and identify potential barriers and facilitators regarding the upcoming implementation of this project, based on the general practitioners' and physiotherapists' perceptions. METHODS: A qualitative study was carried out supported by two focus groups, which were conducted by two researchers. A focus group was carried out with each professional group. One focus group included six general practitioners and the other included six physiotherapists. The focus groups were based on a semi-structured interview schedule, audio-recorded and transcribed verbatim. A thematic analysis was conducted. RESULTS: The participants explored aspects related to the acceptability of the SPLIT project, emphasising the satisfactory amount of effort that is expected to be required for its implementation. Potential facilitators to the implementation of the model were identified, such as the participants`motivation. Potential barriers were also explored, with particular emphasis on the challenges related to the change of routine care. Lastly, the need for particular adjustments in the health services was also highlighted. CONCLUSIONS: This study`s participants highlighted the feasibility and acceptability of the SPLIT project. The identification of potential barriers and facilitators to its implementation also attained major relevance to better prepare the upcoming implementation of this project. The generalizability of findings to the larger population of relevant practitioners is limited, since only two focus groups were carried out. Therefore, this study`s findings should be considered in terms of transferability to contexts that may have some similarities to the context where the study was carried out.